Implementation of Electronic Medical Records (EMR) in Improving the Quality and Efficiency of Health Services: Literature Review - Fazira; Dwi Noerjoedianto (CV. AFDIFAL MAJU BERKAH, 2026)
Background: Digital transformation in Indonesia's health sector, driven by the Industry 4.0 era and mandated by Minister of Health Regulation No. 24 of 2022, requires a transition from manual to Electronic Medical Records (EMR). While promising efficiency, its implementation still faces various practical challenges. Objective: This study aims to analyze the success of EMR implementation, evaluate its impact on work efficiency and service quality, and identify the main obstacles encountered by healthcare facilities. Methods: This study employed a literature review method, analyzing ten scientific articles published between 2022 and 2025. Data were gathered from Google Scholar and national health journal portals, followed by a narrative synthesis.